Qualitative research: specific designs for qualitative research in emergency care?. Issue 11 (22nd October 2009) - Cooper, S; Endacott, R; Chapman, Y
Abstract : This article follows our description of generic qualitative approaches, focusing on the specific designs of ethnography, grounded theory and phenomenology. Distinguishing features are described, including methodological approaches and methods for enhancing rigour. The use of these designs in emergency care is unusual but informative, and important work has been produced. Whether used in a pure or applied manner, it is likely that such approaches will add to our understanding of the emergency world.